Sosialisasi Pembuatan Bio-Compost Sebagai Upaya Pengurangan Sampah Skala Rumah Tangga di Dusun Badu Desa Wanar - Inayah Fitri; Trisnani A; Fita F. Wahidah; Sitti N. Ilmiah; Lilik E; Nur Maulidah (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
The existence of garbage is still a big problem in everyday life. Same as in Badu Dusun, Wanar Village, the garbage problem also disturb the community. It is undeniable that many efforts have been made to deal with this problem, both the government, academics, practitioners of non-governmental organizations, and the wider community. This community dedication aims to provide knowledge and skills for PKK women community in Badu Dusun, Wanar Village in utilizing household waste such as leftover vegetables and fruit peels so that they become appropriate products have economic value and can be applied simply in their respective homes. The method consists of several stages, namely (1) preparing the raw materials, namely, waste, simple composter, decomposer powder (2) the process of socializing bio-compost in their home environment, (3) making bio-compost, and (4) evaluation. The results of community dedication, started to describe of material during socialization the study of compost, organic waste, type of household waste can be used for compost, the correct composting method, the correct method of applaying composting, and an easy method of composting that can be done at home. Overall socialization activities of managing household waste into bio-compost are consideret to be running successfully. The conclusion of community dedication is there are significant differences related to before and after the socialization of the method making bio-compost.